1993
DOI: 10.1093/bja/70.4.440
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nasal Cannulae With Face Mask for Oxygen Administration to Postoperative Patients

Abstract: Thirty postoperative patients were allocated randomly to receive oxygen by Hudson face mask at 4 litre min-1 (group I) or 2 litre min-1 (group II) via nasal cannulae. From 22:00 on the first night after operation, the position of the nasal cannula or face mask was observed for 8 h using video and oxyhaemoglobin saturation (SpO2) recorded simultaneously. In group I the mask remained on and positioned correctly in five patients. In the 10 other patients it was removed a total of 28 times, 17 for nursing tasks, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 5 publications
8
31
0
3
Order By: Relevance
“…(13,(18)(19)(20) In our study, at low oxygen flow rates, the highest FiO 2 values were obtained with Ncath. When oxygen was delivered through Ncan, the FiO 2 was low, which is comparable with the results obtained by Bazuaye et al (14) in seven healthy subjects.…”
Section: Oxygen Therapy Without Nebulizationsupporting
confidence: 49%
“…(13,(18)(19)(20) In our study, at low oxygen flow rates, the highest FiO 2 values were obtained with Ncath. When oxygen was delivered through Ncan, the FiO 2 was low, which is comparable with the results obtained by Bazuaye et al (14) in seven healthy subjects.…”
Section: Oxygen Therapy Without Nebulizationsupporting
confidence: 49%
“…Three patient preference studies comparing nasal cannulae with simple face masks in postoperative care found that patient preference was strongly in favour of nasal cannulae with up to 88% of patients preferring cannulae to masks 289 – 291. Another advantage of cannulae over simple face masks is that they are less likely to be removed accidentally and they allow the patient to speak and eat 290 300. There are no comparisons of these devices in acute care, but there is no reason to believe that the results would be any different for patients requiring medium-dose oxygen therapy.…”
Section: Section 10: Practical Aspects Of Oxygen Therapymentioning
confidence: 99%
“…Three patient preference studies comparing nasal cannulae with simple face masks in postoperative care found that patient preference was strongly in favour of nasal cannulae with up to 88% of patients preferring cannulae to masks 457–459. Another advantage of cannulae over simple face masks is that they are less likely to be removed accidentally and they allow the patient to speak and eat 458 468. There are no comparisons of these devices in acute care, but there is no reason to believe that the results would be any different for patients requiring medium-concentration oxygen therapy.…”
Section: Section 10: Practical Aspects Of Oxygen Therapymentioning
confidence: 99%